Supramolecular synthon transferability and gelation by diprimary ammonium monocarboxylate salts - Das, Uttam Kumar; Puranik, Vedavati G.; Dastidar, Parthasarathi (Crystal Growth & Design, 2012)
Earlier studies revealed that primary ammonium dicarboxylate (PAD) salts possessed gelling ability, and many such salts displayed a 1D columnar hydrogen bonded network (observed in primary ammonium monocarboxylate (PAM) salts) on either side of the dicarboxylate end of the anion. In the present study, a new series of diprimary ammonium monocarboxyate (DPAM) salts have been prepared with the aim of achieving supramolecular synthon transferability (the same 1D columnar hydrogen PAM bonded network on either side of the diammonium cation) in these salts. Single crystal X-ray diffraction studies revealed that, in 47% of the DPAM salts, such supramolecular synthon transferability indeed took place. Some of the DPAM salts also showed gelation ability. The gels were characterized by DSC, rheology, electron microscopy, and atomic force microscopy. Structure property correlation using single crystal and powder X-ray diffraction data on a selected gel was also attempted.